Kontribusi Kepercayaan Diri Terhadap Perencanaan Karir - Indrawati, Khesi Dwi Indrawati (MEDI KONS: Jurnal Prodi Bimbingan dan Konseling UNISRI Surakarta, 2022)
This research is motivated by the low career planning of class XI students, many students have difficulty in planning a career. Students feel confused after graduating to go to college or work, doubtful and unstable in choosing a study program, there are students who have not set a career plan after graduation, many students who choose study programs only follow friends. This makes students less confident in planning a career. The purpose of this study was to determine the correlation between self-confidence and career planning of class XI students of SMA Negeri 1 Kwdungwuni. This type of research is a quantitative research with a correlational research design. The data collection tools used are the self-confidence scale and the career planning scale. The results of the person product moment correlation test, the correlation value of r count is 0.609. While the value of r table for the number of samples is 64 with a significance level of 5% of 0.246. Therefore, r arithmetic 0.609 > r table 0.246, it can be concluded that there is a correlation between self-confidence and career planning for students of class XI SMA Negeri 1 Kedungwuni.